Implementation of Smart Village in Strengthening Socio-Economic and Environmentally Based Waste Management System in Blahkiuh Village, Badung Regency, Bali Province to Support the Achievement of SDGs - Ni Made Anggriyani; Anak Agung Putu Sugiantiningsih; Dewa Ketut Suryawan (Abdi Masyarakat, 2026)
Waste management remains a major challenge in rural areas of Bali due to increasing household activities, tourism development, and changes in consumption patterns. These conditions generate complex social, economic, and environmental problems, particularly in villages with limited institutional capacity and community participation. Desa Blahkiuh, Badung Regency, Bali Province, faces similar challenges in achieving sustainable waste management. The Smart Village approach is considered a relevant strategy to integrate governance, community participation, social innovation, and appropriate technology in addressing local environmental issues. This study aims to analyze the implementation of the Smart Village approach in strengthening a waste management system based on social, economic, and environmental dimensions in Desa Blahkiuh and its contribution to achieving the Sustainable Development Goals (SDGs). This research employs a qualitative descriptive method with a case study approach, using in-depth interviews, observation, and documentation as data collection techniques. The findings indicate that the implementation of Smart Village enhances community participation, increases the economic value of waste through circular economy practices, and improves environmental quality at the village level. These results demonstrate that Smart Village–based waste management contributes to the achievement of SDGs, particularly Goal 11 (Sustainable Cities and Communities), Goal 12 (Responsible Consumption and Production), and Goal 13 (Climate Action).